Kristosentrisme Pneumatik sebagai Tawaran Teologis bagi Spiritualitas Kaum Muda Gereja - Angga Putra Sunjaya (Theologia in Loco, 2022)
ABSTRACT This article discusses qualitative research on youth spirituality in Gereja Bethel Indonesia Bless Impact Generation (GBI BIG) using the investigative method of Christian Smith. The results of this study indicate that young people have a spirituality that is moralistic, therapeutic, and deistic. This article criticizes this moralistic, therapeutic, and deism spirituality from a dogmatic point of view. Through David Wells' Christology view as the theological apparatus, the author believes that moralistic, therapeutic and deistic spirituality will result in failure in the growth of Christian faith because it displaces Christ as the focal point of faith. Complementing Wells' thought, this article brings up the idea of Pneumatic Christocentrism as a theological offering. Keywords: GBI, moralistik, terapeutik, deisme, Pneumatic Christocentrism.